Which methodologies can be used to identify engineering students’ spatial skills? - Charles, Sophie (Mesure et évaluation en éducation)

(untitled) (ADMEE-Canada, 2024)
Research on spatial ability is interested in identifying the cognitive processes which characterise it. It has been related to success in science, technology, engineering, and mathematics. Completed as part of the French research project EXAPP_3D e-FRAN, our study has focused on measuring engineering freshmen’s spatial and 3-D modelling skills. Pen-and-paper tests are currently the most popular method used to measure spatial skills. Our research has shown that performance on these tests is not indicative of the skills targeted by the tests alone: Our first subjects reported a variety of solving strategies. The sensitivity of spatial tests to bypass strategies, in the sense that those used do not correspond to the skills targeted by the test, presents the challenge of defining an experimental protocol that characterises both the performance measured in these tasks, as well as the skills they engage. This article presents a mixed methodology which addresses this twofold issue.